Forming of new educational paradigm of preparation of specialists is on intellectual property in context of requirements of bolonskogo of process - Pererva, P. G.; Kosenko, Oleksandra; Tkacheva, N. P. (Miskolci Egyetem, 2009)
The substantive provisions of on-line tutorial are considered on preparation of specialists in area of intellectual property on the economic faculty of the Kharkov polytechnic university in the light of requirements of the Bolonskogo process and credit-module system of estimation of knowledges.